2018
DOI: 10.1038/s41598-018-23745-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RSK1 activation in malformin-enhanced cellular fibrinolytic activity

Abstract: Pharmacological interventions to enhance fibrinolysis are effective for treating thrombotic disorders. Utilizing the in vitro U937 cell line-based fibrin degradation assay, we had previously found a cyclic pentapeptide malformin A1 (MA1) as a novel activating compound for cellular fibrinolytic activity. The mechanism by which MA1 enhances cellular fibrinolytic activity remains unknown. In the present study, we show that RSK1 is a crucial mediator of MA1-induced cellular fibrinolysis. Treatment with rhodamine-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Similar to the effects on c-Ski, MEK inhibition did not completely reduce the levels of p-ERK, p-CREB or cell proliferation to that of the control group. This phenomenon may be caused by failure of the MEK inhibitor to completely suppress ERK activity, as found in previous studies [22][23][24]. These data indicate that TGF-β1 is an important factor mediating increases in c-Ski through the ERK/CREB pathway.…”
Section: Low Tgf-β1 Concentrations Promote Skin Fibroblast Proliferatsupporting
confidence: 77%
“…Similar to the effects on c-Ski, MEK inhibition did not completely reduce the levels of p-ERK, p-CREB or cell proliferation to that of the control group. This phenomenon may be caused by failure of the MEK inhibitor to completely suppress ERK activity, as found in previous studies [22][23][24]. These data indicate that TGF-β1 is an important factor mediating increases in c-Ski through the ERK/CREB pathway.…”
Section: Low Tgf-β1 Concentrations Promote Skin Fibroblast Proliferatsupporting
confidence: 77%
“…Our recent report showed that fluorescence‐labeled MA1 was enriched in ER‐like intracellular compartments, so, out of the candidate genes, we focused on SQLE localized in ER membrane (Figure G) and validated the effects of depletion by individual sgRNA transduction on MA1 cytotoxicity in U937 cells. Protein expression levels of SQLE were depleted by about 70 % or more after sgRNA transduction (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…MA1 acts on urokinase‐producing monocytes and increases cellular plasmin activity . A recent study also showed that the activation of RSK1 by way of the MAP kinase pathway leads to an increase in urokinase expression for fibrinolytic activity enhancement of MA1 . Although MA1 exhibits undesirable cytotoxicity together with the enhancement of cellular fibrinolytic activity, our previous structure–activity relationship study for MA1 suggested that the cytotoxic effects of MA1 could be split from its fibrinolysis‐enhancing effect .…”
Section: Introductionmentioning
confidence: 99%
“…However, from a pharmaceutical angle, malpicyclins A and C are structurally identical to the cyclopentapeptide plactin B and D, respectively, which were previously isolated from an uncharacterized fungus (38,74) and exhibit fibrinolytic activities by elevating the activity of cellular urokinase-type plasminogen activator (39). The anticoagulating effects of plactins and derived cyclopentapeptides such as malformin A1 are currently under investigation in treatment of thrombic disorders (75). Hence, M. alpina is not only of nutritional benefit by production of polyunsaturated fatty acids, but also of pharmaceutical interest as producer of bioactive natural products.…”
Section: Discussionmentioning
confidence: 99%